2020
DOI: 10.1111/tbed.13567
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Getah virus from pigs in Guangdong province of China

Abstract: Getah virus (GETV) is a mosquito‐borne virus that is widely distributed in Asian countries including China, in which the first case of equine GETV infection was reported in Guangdong province in August 2018. In this study, GETVs were detected in two classical swine fever virus‐positive samples collected from swine herds in Foshan city, Guangdong province, 2018. Infection of porcine PK‐15 cells produced rapid cytopathic effects (CPEs), including shrinking, rounding and detaching, and peak titre of 109.3 TCID50/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…The tropical and subtropical climates of these regions provide a favorable environment for the reproduction of mosquitoes, which play a key role in the spread of GETV among different hosts (30). The existence of GETV-infected animals and mosquitoes in Hunan, Guangdong, and Yunnan provinces, which are the neighboring provinces located in the east and west of Guangxi province, has meant that they are likely to spread, and they have already been reported (23,25,27,28). In this study, we detected and isolated for the first time in Guangxi province, a GETV strain in pig sera using BHK-21 cells, proving the existence of GETV in this region of China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tropical and subtropical climates of these regions provide a favorable environment for the reproduction of mosquitoes, which play a key role in the spread of GETV among different hosts (30). The existence of GETV-infected animals and mosquitoes in Hunan, Guangdong, and Yunnan provinces, which are the neighboring provinces located in the east and west of Guangxi province, has meant that they are likely to spread, and they have already been reported (23,25,27,28). In this study, we detected and isolated for the first time in Guangxi province, a GETV strain in pig sera using BHK-21 cells, proving the existence of GETV in this region of China.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence comparison showed that GX201808 shares high sequence identity at the nucleotide level with the strains HuN1, SD17/09, and JL1808. Group III, represented by the first Chinese strain (M1) that was isolated in 1964 from mosquitoes, contains most GETV strains appearing in mosquitoes, pigs, horses, cattle, foxes, and other animals and has become the dominant viruses circulating among species (17,23,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GETV also represents a potential emerging burden for the pig industry, recently highlighted for China [ 20 ]. Infected piglets show depression, tremors, hind limb paralysis, diarrhea and high mortality, and infection of sows can be associated with abortion [ 21 ]. Live GETV was recently isolated as an adventitious agent contaminating a commercial live-attenuated vaccine for porcine reproductive and respiratory syndrome virus (manufactured in MARC-145 cells) [ 22 ]; perhaps a contributing factor in the increased GETV burden in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The number of cases of GETV-affected mammals has rapidly increased over the last decade. These included pigs in Henan [2011, ( Zhou et al., 2018 )], Hunan [2017, ( Yang et al., 2018 )], Anhui [2017 (available on GenBank but unpublished)], Sichuan [2018, ( Jiang et al., 2019 )], and Guangdong [2018, ( Xing et al., 2020 )], blue foxes in Shandong [2017, ( Shi et al., 2019 )], beef cattle in Jilin [2018, ( Liu et al., 2019 )], and horses in Guangdong [2018, ( Lu et al., 2019 )]. A GETV outbreak occurred on a swine farm in Hunan Province in June and July 2017 and caused many fetal mummies, stillbirths, and piglet deaths ( Yang et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%